2017
DOI: 10.5005/jp-journals-10018-1226
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Therapy in Patients with Nonalcoholic Steatohepatitis in Zagazig University Hospitals

Abstract: Aim:Nonalcoholic fatty liver disease (NAFLD) is probably the most common liver disorder in the world. A subgroup of NAFLD patients is characterized by injury to the hepatocytes and inflammation in addition to excessive fat (steatohepatitis), the latter condition is nominated nonalcoholic steatohepatitis (NASH). This work aimed to evaluate the role of probiotics on the outcome of NASH in patients admitted to the Tropical Medicine Department, Faculty of Medicine, Zagazig University (inpatients and outpatients).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
(23 reference statements)
1
25
0
Order By: Relevance
“…International studies have also observed similar results [56]. An Egyptian study by Abdel Monem with Zigazag University randomized NASH patients to probiotic Acidophilus capsule (2 billion Lactobacillus acidophilus ) or placebo for 17 months and measured improved AST and ALT in treated patients [56]. Wang et al compared the effectiveness of various probiotics with a control in 200 NAFLD patients and measured significantly improved liver function tests in all probiotics groups versus the control, but no significance between them [57].…”
Section: Clinical Use Of Probiotics In Patients With Nafld and Nashsupporting
confidence: 75%
See 3 more Smart Citations
“…International studies have also observed similar results [56]. An Egyptian study by Abdel Monem with Zigazag University randomized NASH patients to probiotic Acidophilus capsule (2 billion Lactobacillus acidophilus ) or placebo for 17 months and measured improved AST and ALT in treated patients [56]. Wang et al compared the effectiveness of various probiotics with a control in 200 NAFLD patients and measured significantly improved liver function tests in all probiotics groups versus the control, but no significance between them [57].…”
Section: Clinical Use Of Probiotics In Patients With Nafld and Nashsupporting
confidence: 75%
“…A 72-NAFLD-patient double-blind study by Nabavi et al compared treatment with 300g/d of probiotic yogurt with Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12 versus conventional yogurt and noted improved hepatic enzymes, total cholesterol, and LDL cholesterol [55]. International studies have also observed similar results [56]. An Egyptian study by Abdel Monem with Zigazag University randomized NASH patients to probiotic Acidophilus capsule (2 billion Lactobacillus acidophilus ) or placebo for 17 months and measured improved AST and ALT in treated patients [56].…”
Section: Clinical Use Of Probiotics In Patients With Nafld and Nashmentioning
confidence: 98%
See 2 more Smart Citations
“…have been reported to reduce gut inflammation and improve gut barrier function by remodeling the gut microbiota [ 119 ]. In humans, administration of Lactobacillus acidophilus reduced AST and ALT levels in NASH patients [ 120 ] and several clinical trials of probiotics were reported in other reviews [ 121 ]. However, most of the molecular mechanisms by which probiotics exert their functions remain unclear.…”
Section: Potential Therapeutic Strategies and Non-invasive Diagnosmentioning
confidence: 99%